Novel [1,2,3]Triazolo[1,5-A]Pyridine Derivatives Are Trypanocidal by Sterol Biosynthesis Pathway Alteration - Moncada-Basualto, M (Future Medicine Ltd., 2019)
Aim: To study a new series of [1,2,3]triazolo[1,5-α]pyridine derivatives as trypanocidal agents because current antichagasic pharmacologic therapy is only partially effective. Materials & methods: The effect of the series upon Trypanosoma cruzi epimastigotes and murine macrophages viability, cell cycle, cell death and on the metabolites of the sterol biosynthesis pathway was measured; also, docking in 14α-demethylase was analyzed. Results: Compound 16 inhibits 14α-demethylase producing an imbalance in the cholesterol/ergosterol synthesis pathway, as suggested by a metabolic control and theoretical docking analysis. Consequently, it prevented cell proliferation, stopping the cellular cycle at the G2/M phase, inducing cell death. Conclusion: Although the exact cell death mechanism remained elusive, this series can be used for the further rational design of novel antiparasitic molecules. © 2019 Newlands Press.